Insect Biodiversity on Inorganic Cayenne Pepper Plants in Plosogeneng Village, Jombang Regency - Mufidah, Khusna Niswatul; Yuliana, Anggi Indah; Nasirudin, Mohamad; Faizah, Mazidatul (AGARICUS: Advances Agriculture Science & Farming, 2024)
The method used in this research is a quantitative method, sampling was carried out by installing Yellow Trap insect traps which were placed at several points for 12 days. The results of this research are the insect diversity index found in this research, there are 5 families, a total of 28 individuals. Consists of Oxyopidae, Coccinellidae, Pentatomidae, Noctuidae and Coreidae. The diversity index (H') value for insects is -1.35. Meanwhile, the dominance index for cayenne pepper plantations in Plosogeneng Village, Jombang District in the Yellow Trap is 0.31. Keywords: Insect Diversity, Dominance Index, Chili Plants.